Immediate Postoperative Pain and Recovery Time after Pulpotomy Performed under General Anaesthesia in Young Children - Sultan Keles; Ozlem Kocaturk (Pain Research and Management)
Background. The aim of this retrospective study was to compare immediate postoperative pain scores and need for rescue analgesia in children who underwent pulpotomies and restorative treatment and those who underwent restorative treatment only, all under general anaesthesia. Methods. Ninety patients aged between 3 and 7 years who underwent full mouth dental rehabilitation under general anaesthesia were enrolled in the study and reviewed. The experimental group included patients who were treated with at least one pulpotomy, and the control group was treated with dental fillings only. The Wong-Baker FACES scale was used to evaluate self-reported pain and need for rescue analgesia. The data were analysed using the Kruskal-Wallis test, two sample t-tests, chi-square tests, and Pearson’s correlation analysis. Results. Ninety percent of the children experienced postoperative pain in varying degrees of severity. Immediate postoperative pain scores in experimental group were found to be significantly higher than in control group (x2=24.82, p<0.01). In the experimental group, 48% of the children needed rescue analgesia, compared with only 13% of the children in the control group (x2=13.27, p<0.05). Conclusion. Children who underwent pulpotomy treatment had higher postoperative pain scores and greater need for rescue analgesia than control group who underwent only dental fillings.